The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1142/s0219887823501530
|View full text |Cite
|
Sign up to set email alerts
|

Scale covariant theory as a dark energy model

Abstract: We consider it worthy if we could construct a realistic model universe that would enable us to identify a clue about the source of dark energy. So, we develop a Scale Covariant Theory model universe considering a 5D spherically symmetric space-time. It is predicted that the constructed model itself behaves as a phantom energy model/source that tends to a de Sitter phase avoiding the finite-time future singularity (big rip). The model universe is isotropic and is free from an initial singularity. The gravitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Vegh introduced the dRGT-like massive theories of the different classes by modification in the reference metric. Considering this theory of massive gravity different classes of the BH solutions have been studied in [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…Vegh introduced the dRGT-like massive theories of the different classes by modification in the reference metric. Considering this theory of massive gravity different classes of the BH solutions have been studied in [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…[40,[43][44][45][46][47][48][49][50][51][52][53] One intriguing aspect of Gaussian states is that the action on the covariance matrix can characterize the transition from one Gaussian state to another. [43,[54][55][56][57] For Bosonic Gaussian states, the non-trivial components of this matrix are symmetric, while they are antisymmetric for Fermionic states. However, we found that the covariance matrix alone is insufficient for calculating Krylov complexity, as it lacks information on the relative phase.…”
Section: Introductionmentioning
confidence: 99%